Электрические параметры и силы электромагнитного вибратора для кристаллизатора машин непрерывного литья заготовок - Виштак, Т.В.; Кондратенко, И.П.; Ращепкин, А.П. (Технічна електродинаміка, 2011)
Mathematical model is developed and numerical calculations of magnetic fields distribution in constructive elements of the accepted execution electromagnetic oscillator with permanent magnets use for system of rocking of continuouscasting machine crystallizer are carried out. Functional relationships of winding interlinkage and oscillator electromagnetic force depending on position of an anchor and a winding current are established. For the accepted design there is defined the electromagnetic force operating on a mobile part of the oscillator. Comparison of electromagnetic force and hydraulic drive force of the equal constructive sizes is carried out.